2018
DOI: 10.1136/medhum-2017-011418
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive frameworks of chronic pain: daily remakings of pain and care at a Somali refugee women’s health centre

Abstract: Pain is an intensely subjective experience and one that is difficult for healthcare professionals to treat. Chronic pain, often diffuse, cyclical and involving many systems of the body, is often not well treated in a medical system that relies on discrete symptoms, identifiable causes, external pathogens and physician specialisation. Pain has its own problems specific to Somali diaspora populations, where chronic pain is prevalent but often undertreated, and where Somali patients face barriers of access to med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(29 reference statements)
2
13
1
Order By: Relevance
“…In our study, health professionals perceived pastoralists, especially those living in faraway places, as having specific health beliefs, a low-level of (biomedical) health literacy and difficulties to express pain. According to Campeau (2018) , explaining one’s pain is challenging, particularly across language and literacy barriers in different healthcare settings. Due to this, building trusting relationships with patients is even more important for health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, health professionals perceived pastoralists, especially those living in faraway places, as having specific health beliefs, a low-level of (biomedical) health literacy and difficulties to express pain. According to Campeau (2018) , explaining one’s pain is challenging, particularly across language and literacy barriers in different healthcare settings. Due to this, building trusting relationships with patients is even more important for health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the ‘divine source’ of all illnesses, Qur’anic healing and prayer are of utmost importance ( Carruth 2014 ). As a study with Somali women revealed, such practices co-existed without conflict ( Campeau 2018 ). Considering this lived medical pluralism among pastoralists and Somalis, a complex phenomenon like pain emphasises the importance of multiple treatment options and interventions.…”
Section: Introductionmentioning
confidence: 99%
“…People who were identified with a disadvantaged standing in social class, migration status, gender and ethnocultural status experienced a poorer pain profile (Brady et al , 2018). Untreated chronic pain among refugees is an indicator of other challenges that refugees experience in a resettled country such as issues of faith and perceived discrimination and exclusion (Campeau, 2018). Physicians and other health-care providers should be aware that patients of refugee status may be experiencing chronic or untreated pain (Brady et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Refugee women are one of the most vulnerable groups in our society and report some of the highest rates of chronic pain [ 11 ]. Whilst people from a refugee background may experience numerous vulnerabilities such as gender inequality, poverty, and social trauma [ 3 ], refugee women are at an increased risk to these vulnerabilities at times of armed conflict, humanitarian crisis, and displacement.…”
Section: Introductionmentioning
confidence: 99%